[Kalibo Ati-atihan, 1995 [videorecording] (NCCA, 1995)
A documentation of the Ati-atihan festival, featuring a parade from the different barangays in costume, the re-enactment of the Barter of Panay and coronation of Ms. Kalibo Ati-atihan '95.